English and Indonesian Idioms of Animals - Mgs. Sulaiman; Indawan Syahri; Muhammad Faisal (Universitas KH. Mukhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2023)
This research was aimed at finding out the similarities, and dissimilarities, as well as possible learning problems faced by the students learning English and Indonesian idioms of animals, and also as the recommendations to TEFL. This research was regarded as descriptive research desig.n To collect the data, the researchers used documentation technique. To analyze the data, the researchers used a descriptive analysis. The results showed that there were two similarities and two dissimilarities between English and Indonesian idioms of animals. The two similarities were in word choices and meanings, while the two dissimilarities were were also in word choices and meanings. The possible learning problems faced by the students learning English and Indonesian were that they were perplexed with the meanings inside the idioms which has implied gloss. The recommendations of this research was as a fundamental teaching guidance in helping English teachers design a better teaching idioms of animals.